Environment and Sustainable Development - Fulekar, M.H.; Pathak, Bhawana; Kale, R K.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
Global society in the 21st century is facing challenges of improving the quality of air, water, soil and environment and maintaining the ecological balance. Environmental pollution, thus, has become a major global concern. The modern growth of industrialization, urbanization, modern agricultural development and energy generation has resulted in discriminate exploitation of natural resources for fulfilling the human desires and need, which have contributed in disturbing the ecological balance on which the quality of our environment depends. Human beings in true sense are the product of their environment. Man-environment relationship indicates that pollution and deterioration of environment has a social origin. The modern technological advancements in chemical processes/operations have generated new products resulting into new pollutants to the abundant level which are above the self cleaning capacity of the environment. One of the major issues in recent times is the threat to the human lives, due to the progressive deterioration of the environment from various sources. The impact of the pollutants on the environment will be significant when the accumulated pollutants load has exceeded the carrying capacity of the receiving environment. Sustainable development envisages the use of natural resources such as forests, land, water and fisheries in a sustainable manner without causing changes in our natural world. Rio de Janeiro-Earth Summit held in Brazil 1992, focuses on sustainable development to encourage respect and concern for use of natural resources in a sustainable manner for protection of environment. This book will be beneficial as a source of educational material to post-graduate, research scholars, teachers and industrial personnel for maintaining the balance in use of natural resources for sustainable development. Book comprises: Green Technology for Sustainable Growth, Sustainable development, Marine Microbial Diversity, Bioprospecting Medicinal plants, Soil Seed Bank Dynamics, Nanotechnology for Environmental Sustainability, Environmental Remediating by Nanoparticles, Biopolymers in Industries, Air Pollution Scenario, Green Federalism, Economic Sustainability, Global warming & Agricultural for Sustainable Development, Green Buildings and Mathematical model in Sustainable development.
Preface -- Contributors -- Emergence of Green Technologies towards Sustainable Growth -- Sustainable Development: An Earnest Hope -- Soil Seed Bank Dynamics: History and Ecological Significance in Sustainability of Different Ecosystems -- Challenges and Prospects in Exploring Marine Microbial Diversity -- Bioprospecting of Plant Essential Oils for Medicinal Uses -- Air Pollution Scenario over Delhi City -- Nanotechnology: Perspective$1 (Bs for Environmental Sustainability -- An Overview of Environmental Remediation using Photocatalyst -- Role of Biopolymers in Industries: their prospective future applications -- Green Federalism: A Historical leap towards Sustainable Human Development -- Economic sustainability in light of consumer behavior: Social Perspectives -- Global warming and agriculture: Industrial Arrangement for sustainable Development -- Green Buildings - Opportunities and Challenges -- Mathematical models in sustainable development -- Index.s
Keywords: Environmental sciences; Waste disposal; Biotechnology; Sustainable development; Pollution; Environment; Environment, general; Sustainable Development; Environmental Engineering/Biotechnology.; Pollution, general; Waste Management/Waste Technology